2009
DOI: 10.1039/b811762d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactivity of metal carbene complexes with heterobiaryl spacer substituents

Abstract: 4 ] to afforded the carbene-carbene coupled olefinic products and small amounts of the corresponding 2-ethyl(biheteroaryl)acetate. By contrast, the biscarbene complex of thienylfuran (15), afforded only the 2,9-diester of thienylfuran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 56 publications
(73 reference statements)
3
28
0
Order By: Relevance
“…[Cr(CO) 5 C(OEt)(2-(N-methylpyrrolyl))] (3) [16] and [Cr(CO) 5 C(OEt)(N-methyl-2-(2'-thienyl)pyrrole)] (4) [38]. Characterization data of 1-4 were in agreement with these literature reports.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…[Cr(CO) 5 C(OEt)(2-(N-methylpyrrolyl))] (3) [16] and [Cr(CO) 5 C(OEt)(N-methyl-2-(2'-thienyl)pyrrole)] (4) [38]. Characterization data of 1-4 were in agreement with these literature reports.…”
supporting
confidence: 85%
“…[Cr(CO) 5 C(OEt)2,2'-thienylfuran] (5) [38] 2,2′-Thienylfuran (0.38 g, 2.5 mmol) was dissolved in tetrahydrofuran (THF) (30 ml) and the solution cooled to -20 °C. 1.7 ml (2.8 mmol) of a 1.6 M solution of n-BuLi in hexane was added and the reaction mixture stirred for 30 minutes.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Thiophene was purified as described in literature, prior to use [11]. The following dimeric heteroarene precursors were synthesized according to known literature methods: 2,2'-Thienylfuran (A) [13] and 4 N-methyl-2-(2'-thienyl)pyrrole (B) [13]. For the carbene complexes, well-known Fischer synthetic methodology was used [1] [20].…”
Section: Generalmentioning
confidence: 99%
“…The detailed synthesis and characterization of most of the complexes of this study have been reported previously [13][14][15][16][17][18][19][20]. Complex (5) was synthesized according to the analogous methoxy complex reported in literature [13] and characterization data are similar.…”
Section: Synthesis Characterisation and X-ray Crystallographymentioning
confidence: 99%